2015
DOI: 10.1177/1352458515610208
|View full text |Cite
|
Sign up to set email alerts
|

The multiple sclerosis-associated regulatory variant rs10877013 affects expression of CYP27B1 and VDR under inflammatory or vitamin D stimuli

Abstract: The MS-associated variant rs10877013 is a genetic determinant that affects the functioning of the vitamin D system linking environmental and genetic factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…In these studies, disease-associated SNPs have been identified in an extended region that contains the CYP27B1 gene as well as neighboring genes that include METTL1 and METTL21B (FAM119B) (56,57). Indeed, some genotypes appear to be preferential for the altered expression of CYP27B1, although observed co-regulation of the METTL21B gene has introduced some complexity.…”
Section: Endocrine Regulation Of Cyp27b1mentioning
confidence: 99%
“…In these studies, disease-associated SNPs have been identified in an extended region that contains the CYP27B1 gene as well as neighboring genes that include METTL1 and METTL21B (FAM119B) (56,57). Indeed, some genotypes appear to be preferential for the altered expression of CYP27B1, although observed co-regulation of the METTL21B gene has introduced some complexity.…”
Section: Endocrine Regulation Of Cyp27b1mentioning
confidence: 99%
“…Some variants had been described in the literature in association with MS that may act through an effect on circulating VD (Alloza et al, ; Australia New Zealand Multiple Sclerosis Genetics Consortium, ; Cortes et al, ; Karaky et al, ; Laursen et al, ; Manousaki et al, ; Orton et al, ; Ramagopalan et al, ; Ramasamy et al, ; Ross et al, ; Scazzone et al, ; Simon et al, ; Sundqvist et al, ; Zhuang et al, ). No significant intergroup differences were observed for presence of these variants in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…The MS risk allele rs2248359-C increases CYP24A1 expression in the frontal cortex but not in white matter of the human brain ( 92 ). This enzyme was also present in DC and 1,25(OH) 2 D 3 -simulated B cells but without a difference between two alleles in tolerizing/pro-inflammatory DC and B cell ( 52 , 108 ). Taken together, the specific mechanism of how these risk SNPs function in different cell types and contribute to the regulation of gene expression and then the etiology of MS is still unclear as are their possible multiple indirect effects on distant genes or long-term effects amplified by other risk factors during cell activation.…”
Section: The Influence Of Vitamin D and Its Complex Metabolism On Msmentioning
confidence: 93%
“…It has been shown in vitro that this haplotype of CYP27B1 is downregulated in tolerizing DC which could point to a role in an autoimmune pathology ( 52 ). And lower CYP27B1 mRNA expression was associated with rs10877013 (C) in LPS + IFNγ-treated monocytes ( 108 ). Unfortunately, another member of this LD METT21B (previously termed FAM119B ) has been shown to be similarly regulated in the same cell types no matter its gene expression from qPCR or its multiple isoforms from RNA-seq, which prevents a clear conclusion ( 52 ).…”
Section: The Influence Of Vitamin D and Its Complex Metabolism On Msmentioning
confidence: 99%